Factors Influencing the Level of Savings Among the Urban Population in Uganda. - Precious Claire Ninsiima (Uganda Christian University, 2023)
This study was carried out to establish the factors that influence the level of savings among the urban population in Uganda. The study objectives aimed at examining the influence of age, inflation rate and type of employment on the level of saving. A cross sectional design was followed using a case of the KCCA Staff SACCO in Kampala and the research was purely quantitative. Questionnaires were distributed to SACCO members and the information obtained was analyzed using Chi square tests, Fisher’s tests and other descriptive statistics to give a proper understanding of the factors that influence saving. The results of the study indicated that age has a positive correlation with saving since savings increased with an increase in age but began to decline towards retirement. Inflation on the other hand was identified as having a negative influence on saving since a decline in saving was attributed to an increase in inflation. Research findings with regard to the impact of employment type on saving were inconclusive. A relationship between type of employment and saving was noticed though its degree and nature of influence remains to be clearly obtained. Thus this study obtained fairly satisfactory results from the field in line with outlined objectives though I would recommend more research on the impact of employment type on saving as well as the influence of anticipated inflation on the current level of saving.
This is a dissertation.